Pengaruh Inflasi dan Kurs Terhadap Investasi di Provinsi Sumatera Utara - Dodi Jese Siburian; Revita Yuni; Henny Mawarta Siregar; Lutfiah Nur Azizah; Meisha Fatma Wijaya; Tessalonika Federova Simanjuntak (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to determine the effect of inflation on investment in North Sumatra Province and to determine the effect of the exchange rate on investment in North Sumatra Province. Using quantitative research. This research was carried out in North Sumatra Province with data from 2000 to 2022 taken through the North Sumatra Province Central Statistics Agency. In this research, the variables used include inflation (X1), exchange rate (X2), and investment (Y). The research data analysis method uses multiple linear regression analysis (Ordinary Least Square) with a significance level of 5%. The research results show that partially the inflation variable has a negative and significant effect and the exchange rate variable has a positive and significant effect on investment in North Sumatra. Furthermore, the inflation and exchange rate variables simultaneously (together) have an influence on investment in North Sumatra.